AKTUALISASI NILAI–NILAI KEMANDIRIAN DALAM MEMBENTUK KARAKTER MANDIRI SISWA - Yusutria Yusutria; Rina Febriana (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
AbstractIslamic boarding schools teach students their self-reliance values, which can shape their personalities in being independent so that they are in accordance with one of the goals of Indonesian education, which is to become independent human beings. For this reason, it is necessary to study the actualization in shaping the character of the independence of their students. This research is field research using a descriptive qualitative approach. The source of data comes from the primary and secondary as well as collecting data through observation, interviews, and documentation. The results of his research can be seen from the factors of awareness, regulation, and habits of being a supporter in shaping independent character, while age and psychology become obstacles in shaping independence in students. The ability to manage finances, time, social life is a reflection of the impact of positive values in the actualization of independence in the independent character of students. Keywords: Actualization; Independence; Character. AbstrakPondok pesantren mengajarkan kepada siswanya nilai-nilai kemandirian, yang dapat membentuk kepribadiannya dalam bersikap mandiri, sehinga sesuai dengan salah satu tujuan pendidikan Indonesia yaitu menjadi insan mandiri. Untuk itu dibutuhkan perlu dikaji tentang aktualisasinya dalam membentuk karakter kemandirian siswanya. Penelitian ini adalah penelitian lapangan dengan menggunakan pendekatan kualitatif deskriptif. Adapun sumber data bersumber dari primer dan skunder serta pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitiannya dapat dilihat dari faktor kesadaran, suritauladan dan kebiasaan menjadi pendukung dalam membentuk karakter mandiri, sementara usia dan spikologi menjadi penghambat dalam membentuk kemandirian dalam diri siswa. Adanya kemampuan dalam mengelola keuangan, waktu, hidup sosial merupakan cerminan akan adanya dampak nilai positif dalam aktualisasi kemandirian dalam karakter mandiri siswa. Kata Kunci: Aktualisasi; Kemandirian; Karakter.